Leadership and Strategy in Educational Administration of Monks in Buriram Buddhist College - Janthathammo (Sa-ardaiem), Phrasurachet; Suerum, Wai (Journal for Developing the Social and Community, 2018)
With the current socio-economic and political changes, work units related to educational institutes have changed their roles to fit the situations and have adjusted themselves to meet their objectives efficiently and effectively. Administrators of educational institutes need to be knowledgeable, understand the situations, and have great vision. They also need to have leadership, emphasizing management to fulfill objectives, relying on co-workers’ co-operation, unity, respect and trust. Under the changing situations, many executives of educational institutes have to review both their roles and roles of their schools regarding their involvement with society. They have done this by examining the needs and the changes in the external environment of the organization at present and then adjusting the organization’s management to meet those needs efficiently and effectively. To be able to do this, it is really necessary for executives of educational institutes to have development plans as well as action plans. They also need to plan how to maximize the use of the organization’s resources. It can be seen that executives of educational institutes who are highly capable are also highly necessary. They need to be mature, knowledgeable, and good at management, both as an art and science. They also need to have leadership. The researcher conducted a qualitative study of leadership and management strategies of the school directors following House and Mitchell’s path-goal theory of leadership effectiveness. According to the theory, there are four types of leader behaviors : achievementoriented, directive, participative, and supportive. Data collection was through in-depth interviews of four major informants and focus groups interviews of 30 teachers and educational personnel of the University. The data was then analyzed and presented descriptively. According to the research results, it was found that each of the University directors practices leadership differently depending on situations. Different situations require different leaders. However, to be effective, leaders need to adjust their leadership style to suit the situations. In addition, leaders can also motivate people by providing clear ways to reach their goals, making it easy enough for people to succeed. Leaders could do this by providing advice, coaching, or acting as mentors. As for management strategies, each of the school directors has their own, focusing on staff development and educational quality development to raise the learning proficiency. To achieve this, teachers or educational staff are provided with academic development and training for educational efficiency and effectiveness.